Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

7x - 3-9x=8-4x+6 what's the Equation to to this​

Sagot :

Answer:

x=5 2/3


Step-by-step explanation:

combine like terms

7x + 4x - 9x= 3x

8 + 3 + 6= 17

3x=17

or

17/3 = 5 2/3

Answer:

x =  [tex]\frac{17}{2}[/tex]

Step-by-step explanation:

7x - 3 - 9x = 8 - 4x + 6 , that is

- 2x - 3 = 14 - 4x ( add 4x to both sides )

2x - 3 = 14 ( add 3 to both sides )

2x = 17 ( divide both sides by 2 )

x = [tex]\frac{17}{2}[/tex]